Determinants of Obesity in Relation to Socioeconomic Status among Middle-Aged Swedish Women - Wamala, Sarah P.; Wolk, Alicja; Orth-Gome´r, Kristina (Preventive medicine, 1997)
Background.It has been previously demonstrated that obesity is common among women with low socioeconomic status (SES), but the factors accounting for this association are not well known. According to our hypothesis, low SES is associated with psychosocial stress, an unhealthy lifestyle, and reproductive history, which may increase the likelihood of women with low SES to be overweight or obese. Methods.We examined overweight and obesity in relation to SES among 300 healthy women ages 30–65 years, who constitute the control group of the Stockholm Female Coronary Risk Study, a population-based case–control study of women with coronary heart disease. This control group was compared with a large population-based sample and found to be representative of healthy Swedish women ages 30–65 years. We used an aggregate of education and occupation as a measure of SES and defined overweight as body mass index (BMI) between 23.8 and 28.6 kg/m2and obesity as BMI > 28.6 kg/m2 Results.Low SES was a strong determinant of overweight and obesity among middle-aged healthy Swedish women. The odds of being overweight or obese increased with lower social position. After adjustment for age, the odds ratios for overweight and obesity among women in a low vs high position were 2.2 [95% confidence interval (CI) 1.1 to 4.4) and 2.7 (95% CI 1.1 to 6.7), respectively. Both low social position and obesity were related to reproductive history (higher parity and earlier age at menarche), unhealthy dietary habits, and unfavorable psychosocial factors (poor quality of life, low self-esteem, and job strain). These factors together explained 53% of the low-SES-obesity association. Conclusions.Reproductive history, unhealthy dietary habits, and psychosocial stress accounted for a large part of the association between low SES and obesity. Dietary habits and psychosocial stress are potentially modifiable factors, which should be taken into account in intervention programs among women with low SES.
Keywords: socioeconomic status; obesity; psychosocial stress; reproductive history; dietary habits; lifestyle; women